Enhanced Magneto-Optical Effect in Heterostructures Composed of Epsilon-Near-Zero Materials and Truncated Photonic Crystals - Hu, Shengyu; Guo, Zhiwei; Dong, Lijuan; Deng, Fusheng; Jiang, Haitao; Chen, Hong (Frontiers in Materials, 2022)
Optical nonreciprocal transmission plays an important role in many applications such as, optical isolation, switching and integrated photonic circuits. However, the nonreciprocity of natural magneto-optical (MO) materials is too weak to be widely used in the actual applications. Magnetized metamaterials enable the exploration of new regime about the MO effect, including the enhanced nonreciprocal transmission and one-way surface waves. In this work, the Fano-type interference effect is studied in the heterostructure composed of a magnetized epsilon-near-zero material and a truncated photonic crystal. The inherent weak MO activity is significantly enhanced in the heterostructure because of the field intensity enhancement mechanism and Fano-interference. The results provide a way to design novel optical nonreciprocal devices with excellent performance by using metamaterials.